2018
DOI: 10.3390/diagnostics8030061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Plastic of the Realistic GeePS-L2S-Breast Phantom

Abstract: A breast phantom developed at the Supelec Institute was interrogated to study its suitability for microwave tomography measurements. A microwave measurement system based on 16 monopole antennas and a vector network analyzer was used to study how the S-parameters are influenced by insertion of the phantom. The phantom is a 3D-printed structure consisting of plastic shells that can be filled with tissue mimicking liquids. The phantom was filled with different liquids and tested with the measurement system to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Those phantoms are cheap, easy to alter, reusable and stable. They require, however, plastic mould materials which can cause disturbances in the scattered signals [39].…”
Section: Phantoms Preparation and Characterizationmentioning
confidence: 99%
“…Those phantoms are cheap, easy to alter, reusable and stable. They require, however, plastic mould materials which can cause disturbances in the scattered signals [39].…”
Section: Phantoms Preparation and Characterizationmentioning
confidence: 99%
“…The numerical model obtained from the CT presented intricate morphological details due to the intrinsic complexity of the anatomical structures. Given that we aimed to produce a phantom compatible with 3D-printing technology, we reduced the complexity of some details of the model, in order to reduce the amount of polymer of the fabricated phantom, thus mitigating the possible influence of polymer in microwave measurements [ 60 ]. We ensured that the main features of the phantom were still present in the final phantom, and only small details were reduced or removed.…”
Section: Axillary Phantom Design and Developmentmentioning
confidence: 99%
“…Indeed, on one hand, a 1.5-mm thickness is not sufficient to ensure a perfect waterproofing of the phantom, but leakages can be avoided by smoothing the structure by means of acetone vapor and by coating it with epoxy resin. On the other hand, despite their thinness, it has been experimentally [37] and numerically [38] shown that due to the high dielectric contrast with respect to the various biological tissues, the ABS walls perturb the field significantly. Concerning the breast structure, a solution proposed in Reference [29] consists of using conductive ABS whose dielectric parameters (i.e., ϵr10 and σ0.4 S/m at 2.45 GHz, see [29]) are closer to that of adipose tissues (ϵr5 and σ0.1 S/m, see Table 1) than the normal one.…”
Section: The Phantomsmentioning
confidence: 99%